2016
DOI: 10.1111/bju.13537
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prostate cancer survival in Germany and the USA: can differences be attributed to differences in stage distributions?

Abstract: The survival increase in Germany and the survival advantage in the USA might be explained by differences in incidence and stage distributions over time and across countries. Effects of early detection or a lead-time bias due to the more widespread utilisation and earlier introduction of PSA testing in the USA are likely to explain the observed patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…However, in the Munich Cancer Registry, the number of men under AS/WW was around 20% in both periods, whereas we observed about 28% in the Canton of Zurich. Evaluating the RS of PCa patients in Germany revealed an overall 10-year RS of 91% [22,23], and studies based on US SEER data observed a 10-year RS of PCa patients between 95 and 100% [23,24]. The RS in our study is comparable with that observed in Germany, but is lower than in the US.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, in the Munich Cancer Registry, the number of men under AS/WW was around 20% in both periods, whereas we observed about 28% in the Canton of Zurich. Evaluating the RS of PCa patients in Germany revealed an overall 10-year RS of 91% [22,23], and studies based on US SEER data observed a 10-year RS of PCa patients between 95 and 100% [23,24]. The RS in our study is comparable with that observed in Germany, but is lower than in the US.…”
Section: Discussionsupporting
confidence: 74%
“…The RS in our study is comparable with that observed in Germany, but is lower than in the US. Different incidence and stage distributions in the US and Germany may partly explain these differences [23]. In the US, PSA screening was used more frequently and introduced earlier compared with Switzerland or Germany.…”
Section: Discussionmentioning
confidence: 99%
“…We did not compared the difference of MIR improvement between countries according to the expenditures in the health care system. However, previous studies had shown the advantages of survival rate of developed countries such as America and European countries717. It is no doubt that, in recent years, limited improvement of survival rate in prostate cancer was achieved but they still had better MIRs compared with those countries with low expenditures in the health care system which were shown in our results717.…”
Section: Discussionsupporting
confidence: 51%
“…This means that besides the dietary, genetic, and environmental contributions of prostate risk, early screenings and advanced surgical and personalized therapy play important roles in improving clinical outcomes which contribute to low MIR15141516. An observation study found that early detection or a lead time bias of more widespread utilization and earlier introduction of PSA testing in America would cause the differences in incidence and stage distributions over time which would influence the survival7. Early detection and appropriate treatments including the advanced surgical intervention equipment and personalized therapies lead to large expenditures in the health care system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation